THE IMPORTANCE OF ENGLISH SKILL IN OPERATIONAL DEPARTMENTS IN HOTEL - Salma Permana, Michelle (Melekliterasi Press, 2023)
This study aims to analyze the level of the importance of English skill in operational departments from the point of view of a hotel employee. This research is qualitative research since the data obtained are in a form of description which is in non-numerical data that focuses on the study of meaning. The data are collected through questionnaire with closed ended questions. The research findings show that from seven English skills, there are four highest perceived importance skills to have as an operational department employee. They are listening skill, speaking skill, writing skill, and grammar in speaking skill.